CASE STUDY: FEMALE ENTREPRENEURSHIP INCLUSIVE MANAGEMENT OF LUIZA HELENA TRAJANO AT MAGAZINE LUIZA - Grutmann, Phayra Kaoma; Rodrigues, Daniel Henrique; Silva, Renata (Seven Editora, 2025)
Luiza Trajano's management case is an inspiring example of entrepreneurship and inclusive management. Through her leadership, Luiza Trajano managed to transform Magazine Luiza into one of the largest retail chains in Brazil, earning national and international recognition. One of the key results of this case is the proof that inclusion in management is a competitive advantage for companies. Luiza Trajano understands that a country where everyone advances prospers. That said, her actions and programs are geared towards the growth of the population as a whole, but especially for women and small businesses. Entrepreneurship can overcome obstacles related to crises and the lack of adequate public management, provided there is inclusive management that values and promotes equal opportunities. Luiza Trajano is an example of how inclusive management can contribute to diversity and innovation in a company. Magazine Luiza stands out not only for its financial results but also for its socially responsible actions. This case reflects the results that entrepreneurship combined with inclusive management can bring in times of crisis, both for the organization and for society as a whole.DOI: https://doi.org/10.56238/sevened2025.029-034